THE IMPACT OF ARTIFICIAL INTELLIGENCE ON MODERN TRANSLATION PRACTICES (KONFERENSIYA, 2025)
This article examines how artificial intelligence has affected contemporary translation techniques, emphasising the development of neural machine translation and AI-assisted workflows. According to the study, AI greatly improves accessibility, terminology consistency, and translation speed. However, it also identifies key limitations, particularly in handling cultural nuances, figurative language, and context-dependent meanings. The findings emphasize that AI cannot fully replace human translators but instead functions as a supportive tool that reshapes their roles toward editing, quality control, and decision-making. The article concludes that the future of translation lies in effective human–AI collaboration